CIRCA: Circadian inference of rhythmicity using comparative analysis from non-invasive continuous measurements of cortisol and melatonin in passive perspiration - Annapoorna Ramasubramanya; Preeti Singh; Kai-Chun Lin; Shalini Prasad; Sriram Muthukumar (Biosensors and Bioelectronics: X, 2025)
Cortisol and melatonin exhibit distinct circadian rhythms crucial for the regulation of stress and sleep-wake cycles. Precise and continuous evaluation of differential rhythmicity is essential for understanding and managing circadian health; however, current methods using salivary samples are inconvenient for continuous use and dynamic monitoring. In this work, we demonstrate the continuous and dynamic monitoring of cortisol and melatonin using a sweat based wearable sensor based on passive perspiration. Salivary levels mapped with sweat concentrations at sample collection times exhibited strong relationships (Pearson r = 0.92 for cortisol and r = 0.90 for melatonin), and Bland-Altman analysis verified matrix agreement (mean bias close to zero with narrow limits of agreement of −6.09 to 5.94 ng/mL for cortisol and −7.54 to 10.77 pg/mL for melatonin). CircaCompare was used to establish differential rhythmicity, and the results showed two separate peak phases: melatonin at 2AM and cortisol at 8AM when aggregated for all subjects; however, the phases and amplitudes shifted when the results were analyzed by age and by sex validating the dynamic expressions vary by subject and the importance of continuous monitoring of these circadian biomarkers. This study is the first to demonstrate that a passive perspiration based biosensing that continuously measures cortisol and melatonin would help stratify age-related and potentially environment/life-style related changes in hormonal phase and amplitude expression of the circadian biomarkers. Our research establishes sweat as an effective alternative to saliva for endocrine monitoring, facilitating tailored circadian health management, wearable chronotherapy, and continuous hormonal diagnostics.